2005
DOI: 10.1002/nbm.968
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic differences between primary and recurrent human brain tumors: a 1H NMR spectroscopic investigation

Abstract: High-resolution proton magnetic resonance spectroscopy was performed on tissue specimens from 33 patients with astrocytic tumors (22 astrocytomas, 11 glioblastomas) and 13 patients with meningiomas. For all patients, samples of primary tumors and their first recurrences were examined. Increased anaplasia, with respect to malignant transformation, resulting in a higher malignancy grade, was present in 11 recurrences of 22 astrocytoma patients. Spectroscopic features of tumor types, as determined on samples of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 45 publications
6
69
1
Order By: Relevance
“…This partially explains the fact that we have a pronounced overlap between the spectra of different tumor groups. Even with these limitations, using both manual and semi-automatic analyses, we found a metabolic pattern in tumors and controls that was consistent with recent studies (3,4,6,7,(23)(24)(25)(26)(27). Tumors showed a reduction in the levels of NAA and creatine and an increase in the levels of choline, compared to normal tissue.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This partially explains the fact that we have a pronounced overlap between the spectra of different tumor groups. Even with these limitations, using both manual and semi-automatic analyses, we found a metabolic pattern in tumors and controls that was consistent with recent studies (3,4,6,7,(23)(24)(25)(26)(27). Tumors showed a reduction in the levels of NAA and creatine and an increase in the levels of choline, compared to normal tissue.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have been conducted to assess the metabolic patterns of brain tumors in an attempt to correlate them with the histology of the tumor, aggressiveness, and clinical outcome (4)(5)(6)(7)(8)(9)(10)(11)(12). Some studies have compared different kinds of spectral fitting methods, either in the time (13) or frequency domain (14).…”
Section: Introductionmentioning
confidence: 99%
“…31 Several methods, including positron-emission tomography, perfusion MR imaging, and MR spectroscopy, have been proposed to study tumor grading and malignant progression in glial neoplasms. [32][33][34][35][36][37] Spectroscopic methods in particular may be useful in eliciting the metabolic correlates of genetic progression of gliomas or the malignant potential of meningiomas 38,39 during follow-up neuro-oncologic imaging. The role of decreasing ADC as a biomarker of worsening histologic grade has been less widely studied in intracranial neoplasms [40][41][42] (M.S.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that glycine administration to schizophrenia patients improves the NMDA receptor function [2]. Furthermore, elevated levels of glycine have been observed in brain tumors and glycine possibly represents a marker for tumor malignancy [3,4]. Thus, it is of great interest to explore non-invasive methods to measure brain glycine.…”
Section: Introductionmentioning
confidence: 99%